Dataset associated with the Colorado Agriculture Bibliography NEH & USAIN Project - Level, Allison V.; Standish, Sierra (Colorado State University. Libraries, 2023)
As family farms disappear from the landscape, most Americans do not have contact with the agricultural roots of the country. More than ever, the historical literature that helps in telling the story of American farming needs protection. The Preserving the History of United States Agriculture and Rural Life Project, administered by Cornell University, calls for states to identify and list important agricultural literature for preservation purposes. This paper discusses the Colorado project and highlights the scope and identification of materials and the organization of a Web-searchable bibliographic database. Because Colorado began to participate after approximately half of the states had completed bibliographies, staff could access already-tested methodologies for scope descriptions, subject headings, and other "how-to" processes. By using the lessons learned by others, staff were able to expand the scope, capture extra records, and design a nuanced Web site as a portal to the bibliography.
The Colorado Agriculture Bibliography of Primary and Secondary Material Published 1820-1945 was part of a NEH grant project with research conducted 2004-2007. The dataset includes bibliographic information (i.e. title, author, format-book, photograph archival collection, subject headings, etc.) for about 16,000 records about Colorado’s agricultural and rural past. Some items were later digitized and placed in the CSU Library digital repository (see: https://archives.mountainscholar.org/digital/collection/p17393coll63). Items with a link (URL/permlink) are available as full-text. The topics covered in this project are varied but include agriculture, education, water, mining, tourism, recreation, and more. The bibliography contains information about but not full-text for books, journals, dissertations, theses, archival collections, maps, photos, pamphlets, and more. The Web site and bibliography reflects Colorado’s contribution to the Preserving the History of United States Agriculture and Rural Life Project. This nation-wide effort aims to identify and preserve state and locally significant literature. The project involves the National Endowment for the Humanities (NEH), Cornell University, the United States Agricultural Information Network (USAIN), the National Agricultural Library (NAL), and other land-grant universities.
Keywords: Colorado agriculture bibliography; rural life and agricultural topics; NEH; USAIN; Colorado State University; Colorado Agbib; CO